Girl-only clubs' influence on SRH knowledge, HIV risk reduction, and negative SRH outcomes among very young adolescent girls in rural Malawi - Wanangwa Chimwaza Manda; Nanlesta Pilgrim; Mphatso Kamndaya; Sanyukta Mathur; Yandisa Sikweyiya (BMC, 2021)
Abstract Background Early adolescence is an important period to lay the foundation for positive sexual health development that can overcome sexual and reproductive health (SRH) challenges faced by very young adolescents (VYAs) as they reach puberty and sexual debut. In this study, we explored the following questions: first, what are the experiences of VYA girls on DREAMS' Go Girl club participation? Second, how does club participation influence the VYAs SRH knowledge to reduce their risk for HIV and negative sexual health outcomes? Methods This was a qualitative study in which twenty-three in-depth interviews were conducted with VYA girls aged 12-14 years. These girls were enrolled in girl-only clubs in two rural southern districts in Malawi. The clubs were a part of larger comprehensive HIV prevention project called DREAMS (Determined, Resilient, Empowered, AIDS-free, Mentored, and Safe) which provided an evidence-based core package of interventions to VYAs to prevent HIV. Interventions included improved access to key health services, education support, social skills, asset building, and economic strengthening. Narrative inquiry was used to generate first-hand accounts of the girls' experiences with club participation. Thematic analysis was used to generate themes from the transcribed stories. Results Six main themes were generated: 1) reasons for joining the clubs with desire to learn about SRH as a motivation for joining the clubs.; 2) influence on gender norms and roles whereby participants described a change of gender roles and norms at home; 3) influence on child abuse practices whereby participants reported a decline in child abusive practices at home;4) influence on life skills and social networks whereby participants described learning about networking; 5) support to go back to school whereby out-of-school girls described how economic empowerment of their guardians facilitated their return to school; and 6) influence of clubs on SRH knowledge acquisition and behaviours whereby participants described acquiring knowledge on sexual health issues. Conclusion Girls-only HIV and SRH programs coupled with economic empowerment for their families can be effective in keeping VYA girls in school and improving SRH knowledge and health seeking behavior.